2010
DOI: 10.1007/978-3-642-17358-5_43
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Configuration of Web Service Monitors

Abstract: Service monitoring is required for meeting regulatory requirements and verifying compliance to Service Level Agreements (SLAs). As such, monitoring is an essential part of web service-based systems. However, service monitoring comes with a cost, including an impact on the quality of monitored services and systems. To deliver the best value to a service provider, it is important to balance meeting monitoring requirements and reducing monitoring impacts. We introduce a novel approach to configuring the web servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…We have previously described a brute force Optimization Routine, which finds an Optimal Monitoring Configuration by enumerating the search space of monitoring configurations, and calculating the utility for each [2]. Since we intend for optimization to be performed at intervals as low as one hour, the computation time of the enumerative optimization routine is not acceptable, as the largest search space that the enumerative optimization routine will search in an hour allows for only small-to-medium systems, of up to approximately 5 monitors.…”
Section: B Heuristic-based Optimization Routinementioning
confidence: 99%
See 2 more Smart Citations
“…We have previously described a brute force Optimization Routine, which finds an Optimal Monitoring Configuration by enumerating the search space of monitoring configurations, and calculating the utility for each [2]. Since we intend for optimization to be performed at intervals as low as one hour, the computation time of the enumerative optimization routine is not acceptable, as the largest search space that the enumerative optimization routine will search in an hour allows for only small-to-medium systems, of up to approximately 5 monitors.…”
Section: B Heuristic-based Optimization Routinementioning
confidence: 99%
“…2 The monitoring level is the amount of monitoring performed, and may relate to properties such as sampling rates or resolution 4) Configuration Manager: The Configuration Manager maintains a database of available Monitors used to send individual Monitoring Settings to each Monitor. A translation table allows for translation of terms that may be monitor specific, e.g.…”
Section: A Optimization Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of the exiting work has properly considered the resource cost, which should not be neglected, especially when cost-effective monitoring is required. Furthermore, monitoring also incurs system cost [28], [59]. Monitoring strategy formulation must consider both the benefit and cost of monitoring.…”
Section: Related Workmentioning
confidence: 99%
“…As demonstrated in [59], those operations can result in up to 70 percent performance overhead, slowing down the services and systems. Our previous experiments have also identified that a monitor can cause as much as 40 percent; performance overhead on a web service under certain circumstances [28], [29].…”
mentioning
confidence: 96%